I am a Child. Hypothesis on Spectator Pedagogy - Kirkkopelto, Esa (ETHICS IN PROGRESS, 2011)
The paper consists of series of suggestions and historical references on the basis of which it would become possible to think and practice „spectator pedagogy” in performing arts. Contemporary performance practices can claim for new kind of political relevance by focusing on the way spectator´s corporeal experience changes during and through theatrical situation. Naive body produced by a performance is also most susceptible for thoroughgoing political and ecological change. This is the first outline by its author on this topic.